Efficacy of SAD (Berne) rabies vaccine given by the oral route in two species of jackal (Canis mesomelas and Canis adustus) - Bingham, J.; Kappeler, A.; Hill, F.W.G.; King, A.A.; Perry, Brian D. (Wildlife Disease Association, 1995)
Eight black-backed jackals and seven side-striped jackals were given SAD (Berne) rabies vaccine by direct oral instillation. Three different vaccine doses were used: 106.3, 106.8 and 107.5 median tissue culture infectious doses. Two additional jackals were given vaccine in chicken heads. One group of jackals was challenged with a lethal dose of jackal-derived rabies virus 1 month and a second group 12 months after vaccination. All 17 vaccinated jackals developed high and persistent serum neutralizing antibody titres. All challenged jackals resisted a lethal dose of rabies virus, whereas 3 control jackals given the same challenge developed rabies.